Relationship between microstructure, hardness, XRD, TGDTA analysis, and wear performance of a Cast ZA Alloy - Kaplan, Mehmet; Ileriturk, Musa; Balalan, Zuelkuef (Taylor & Francis Inc, 2008)
In the present article, microstructure, hardness, X-ray diffraction (XRD), thermal gravimetric and differential thermal analysis (TGDTA), and wear performance of a Cast ZA Alloy were studied by using scanning electron microscopy (SEM), XRD analysis, thermal gravimetric and differential thermal analysis and tensile strength, hardness, and wear test techniques. Wear performance of the alloy was investigated on a pin-on-disk wear tester under dry sliding conditions, rubbing against nitrided steel. The wear performance of some specimens was superior to others, for which microstructure and precipitated particulates were important. It has showed that some important phases occurred and improved the wear performance after solution-treatment.
Keywords: alpha-Al; beta-Zn; casting; CuZn5 (epsilon); differential thermal analysis; energy dispersive X-ray spectrograph; eta-Zn; hardness; mechanical properties; microstructure; oxidation behavior; phase structure; reagent for etching; scanning electron microscopy; tau ' phases; thermal gravimetric analysis; wear; X-ray diffraction; ZA alloy